Bio-Priming Using Indigenous Pseudomonas Fluorescens To Improve Local Upland Rice (Padi Gogo) Production Of Paebiu Kolopua And Pae Wuna Cultivars - Asri Razad; Gusti Ayu Kade Sutariati; Tresjia C Rakian; Jendri Mamangkey; Marina Silalahi (International Journal of Science, Technology & Management, 2021)
Research was performed to evaluate the effect of biopriming technique using indigenous rhizobacteria in improving local upland rice from Southeast Sulawesi. Randomized group design was applied in this research using factorial pattern consisting of 2 factors. The first factor was upland rice cultivars consisting of 2 (two) levels of Paebiu Kolopua (V1) and Pae Wuna (V2) cultivars. Meanwhile, the second factor was rhizobacteria isolates, consisting of 4 (four) levels, those are without rhizobacteria treatment (R0), KNS11 isolate (R1), KLKU02 isolate (R2) and KNW11 isolate (R3). Research results indicated that interaction between Paebiu Kolopua cultivar and KLKU02 isolate treatment significantly affected plants height with 29.22% improvement and the amount of rice per panicle with 176.33% improvement compared to the control. Therefore, KLKU02 isolate can be recommeded as the best treatment to improve the production and outcome of local upland rice plant.